2022
DOI: 10.1109/access.2022.3193938
|View full text |Cite
|
Sign up to set email alerts
|

AI-Based Personalized E-Learning Systems: Issues, Challenges, and Solutions

Abstract: A personalized e-learning system is effective in imparting enhanced learning to its users. As compared to a conventional e-learning system, which provides similar contents to each learner, a personalized learning system provides specific learning contents and assessments to the learners. Personalization is based on Artificial Intelligence (AI) based techniques in which appropriate contents for each learner are determined using the level of comprehension of the learner and the preferred modes of learning. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 139 publications
0
7
0
1
Order By: Relevance
“…The findings of this study present an overview of the research fronts and intellectual bases, as well as the evolution of research hotspots and recent trends in the field of AI-supported personalised learning. They complement related reviews which addressed AI in education in general (Chen et al, 2020b;Murtaza et al, 2022) or specific areas such as relevant technologies (Chu et al, 2022) and subject disciplines (Hwang and Tu, 2021), by highlighting the evolution of research on personalisation in learning with the support of advances in AI along the years.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The findings of this study present an overview of the research fronts and intellectual bases, as well as the evolution of research hotspots and recent trends in the field of AI-supported personalised learning. They complement related reviews which addressed AI in education in general (Chen et al, 2020b;Murtaza et al, 2022) or specific areas such as relevant technologies (Chu et al, 2022) and subject disciplines (Hwang and Tu, 2021), by highlighting the evolution of research on personalisation in learning with the support of advances in AI along the years.…”
Section: Discussionmentioning
confidence: 97%
“…Chen et al (2022a) examined the research topics related to AI applications in education and identified the trends of the topics along the years and future directions. The review of Murtaza et al (2022) addressed the development of AI-based personalised e-learning by surveying relevant systems which feature the provision of specific learning contents and assessments to learners according to their knowledge level and preferred mode of learning and summarising the learning models and theories as well as the requirements and challenges involved in these systems.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…AI-integrated personalization is a method in which suitable content for each learner is established by grasping the learner's understanding and his or her preferred mode of learning. It is quite different from the traditional e-learning system, which provides similar content (Murtaza, Ahmed, Shamsi, Sherwani, & Usman, 2022). Learning abilities vary from one student to another.…”
Section: Personalized Learning Journeymentioning
confidence: 96%
“…Reference source not found., AI algorithms are employed to collect and analyse data on how students interact with learning materials and assessments. This data is then used to create a profile of each learner's progress and comprehension [46]. Based on this profile, the system can recommend suitable learning resources, adjust the level of difficulty, and provide targeted feedback to help students overcome challenges and reinforce their strengths [47].…”
Section: Adaptive Learning Systemsmentioning
confidence: 99%